A Successful Treatment of Hemifacial Spasm After Flow Diverter Stent Placement for Ipsilateral Internal Carotid Artery Saccular Aneurysm - Muhtaroglu, Ferda Selcuk; Kamiloglu, Belin; Muhtaroglu, Musa (Journal of Medical Cases, 2025)
Hemifacial spasm (HFS) is a neurological disorder characterized by involuntary, paroxysmal contractions of the muscles innervated by the facial nerve on one side of the face. While primary HFS is most often caused by vascular compression at the root exit zone (REZ) of the facial nerve, secondary causes such as tumors, arteriovenous malformations, and intracranial aneurysms are rare. The management of HFS due to aneurysmal compression remains challenging, and the literature on endovascular treatment, particularly with flow diverter stents, is limited. We report the case of a 56-year-old woman with a history of diabetes mellitus type 2, hypertension, and hypercholesterolemia, who presented with progressive right-sided HFS. Imaging revealed a saccular aneurysm of the right internal carotid artery (ICA) at the cavernous-ophthalmic segment. The patient underwent successful endovascular treatment with a Derivo embolization device (DED) flow diverter stent. Her HFS resolved completely post-procedure, with no neurological deficits or recurrence at 6-month follow-up. This case highlights the efficacy of flow diverter stent placement for HFS caused by ICA saccular aneurysm and represents the first such report from Northern Cyprus. The case underscores the importance of considering secondary etiologies in atypical HFS and demonstrates the therapeutic potential of endovascular flow diversion in this context.